SYSTEMATIC LITERATURE OF THE INFLUENCE OF LEADERSHIP STYLE ON ORGANIZATIONAL BEHAVIOR THROUGH MOTIVATION - Witjaksono Adi Pangestu; Victorio Chipta Gregory Manus; Sopiah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Studi This study systematically analyzes the relationship between leadership styles and organizational behavior, with work motivation as an intervening variable. The method employed is a Systematic Literature Review (SLR) based on the PRISMA protocol, analyzing 50 scholarly articles published in Scopus-indexed journals over the last five years (2020–2025). The analysis reveals that transformational, authentic, entrepreneurial, paternalistic, and inclusive leadership styles significantly influence organizational behavior. Work motivation—whether intrinsic, extrinsic, or prosocial—serves as the primary psychological mechanism bridging the impact of leadership styles on such behavior. A theoretical synthesis is constructed through the integration of Full Range Leadership Theory, Self-Determination Theory, and Expectancy Theory, which is then formulated into an interactive conceptual model. This study contributes theoretically by expanding the multidimensional understanding of the relationships among organizational variables while offering practical implications for developing value-based leadership strategies and work motivation systems. The research also uncovers several gaps, including methodological limitations in longitudinal studies, geographic biases, and insufficient exploration of contemporary leadership styles. Recommendations are directed toward strengthening multilevel research designs, expanding the scope to informal sectors, and integrating interdisciplinary approaches.